Simulating forensic casework scenarios in experimental studies: The generation of footwear marks in blood. (July 2016) - McElhone, Rachel L.; Meakin, Georgina E.; French, James C.; Alexander, Tracy; Morgan, Ruth M.
Highlights: Variables affecting the appearance of blood-based footwear marks are investigated. Specific combinations of footwear tread and blood dryness affect mark quality. Marks in human blood tend to be of better quality than those in equine blood. Results narrow possible explanations for a contentious bloodstain in a case example. Experimental studies are valuable for developing an evidence base for interpretation. Abstract: A study was designed to investigate the effects of external variables, including blood type, flooring surface, footwear tread depth and blood dryness, on the appearance of blood-based footwear marks, with particular reference to simulating a specific casework scenario. Results showed that footwear marks left in human blood tended to be of greater quality than those in equine blood, highlighting a potential issue in applying data generated with equine blood to human bloodstains in casework. Footwear tread effects were also dependent on blood type, but the type of flooring surface did not affect the appearance of the mark. Under some conditions, as the blood dried, the amount of detail retained from footwear contact decreased. These results provide the beginnings of an empirical evidence base to allow a more accurate interpretation of blood-based footwear marks in forensic casework. When applied to a disputed bloodstain in a specific case, these results also demonstrate the importance of such experiments in narrowing the range of explanations possible in the interpretation of forensic evidence.